EFFECTIVE STRATEGIES FOR TEACHING ENGLISH TO PRESCHOOL CHILDREN (American Journal of Interdisciplinary Research and Development, 2023)
Preschool is a magical time when young minds are like sponges, eager to soak up knowledge and language. Introducing English to preschoolers can be a rewarding and enriching experience, providing them with a valuable skill for their future endeavors. This article explores the importance of teaching English to preschool children, delving into effective strategies that educators and parents can employ to create a nurturing environment for language acquisition.